A carceral ecology Ushuaia and the history of landscape and punishment in Argentina - Edwards, Ryan C. 1984- (University of California Press, 2022)
"Closer to Antarctica than to Buenos Aires, the port town of Ushuaia, Argentina is home to a national park as well as a museum that is housed in the world's southernmost prison. Ushuaia's radial panopticon operated as an experimental hybrid penal colony and penitentiary from 1902-1947, designed to revolutionize modern prisons globally. A Carceral Ecology offers the first comprehensive study of this notorious prison and its afterlife, documenting how the Patagonian frontier and timber economy became central to ideas about labor, rehabilitation, and resource management. Mining the records of penologists, naturalists, and inmates, Ryan C. Edwards shows how discipline was tied to forest management, but also how inmates gained situated geographical knowledge and reframed debates on the regeneration of the land and the self. Bringing a new imperative to global prison studies, Edwards asks us to rethink the role of the environment in carceral practices as well as the impact of incarceration on the natural world"--
Keywords: Gefängnis; Strafkolonie; Umwelt; Forstwirtschaft; Ushuaia; Prisons / Argentina / Ushuaia / History / 20th century; Prisons / Environmental aspects / Argentina / 20th century; Prisons / Argentine / Ushuaia / Histoire / 20e siècle; Prisons / Aspect de l'environnement / Argentine / 20e siècle; HISTORY / Latin America / General; SOCIAL SCIENCE / Criminology; Prisons; Prisons / Environmental aspects; Argentina; Argentina / Ushuaia; 1900-1999; History